2020
DOI: 10.21203/rs.3.rs-20633/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrasonic bone scalpel for thoracic spinal decompression: case series and technical note

Abstract: Background: Thoracic spinal stenosis (TSS) is a rare but intractable disease that fails to respond to conservative treatment. Thoracic spinal decompression, which is traditionally performed using high-speed drills and kerrison rongeurs, is a time-consuming and technically challenging task. Unfavorable outcomes and high incidence of complications are the major concerns. The development and adaptation of ultrasonic bone scalpel (UBS) has promoted its application in various spinal operations, but its application … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Sun et al . augmented the surgical procedure by maintaining the last thin layer of ossification rather than penetrating it, reducing the incidence of UBC‐related nerve root injuries significantly 22 , while Tang et al . suggested breaking the distal end of the plaque to press it down slightly and separating the adhesion with direct vision under the microscope to minimize disturbance to the spinal cord 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sun et al . augmented the surgical procedure by maintaining the last thin layer of ossification rather than penetrating it, reducing the incidence of UBC‐related nerve root injuries significantly 22 , while Tang et al . suggested breaking the distal end of the plaque to press it down slightly and separating the adhesion with direct vision under the microscope to minimize disturbance to the spinal cord 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, as a result of ventral adhesion separation of the dural sac and the surgical instrument prying anterior ossification, electrophysiological early warning events occurred sometimes 16,17 . Sun et al augmented the surgical procedure by maintaining the last thin layer of ossification rather than penetrating it, reducing the incidence of UBC-related nerve root injuries significantly 22 vision under the microscope to minimize disturbance to the spinal cord 17 . Despite this, surgical instruments are still used to gouge or rotate the ossification beneath the spinal cord.…”
Section: Current Status Of Traditional Circumferential Decompressionmentioning
confidence: 99%
See 1 more Smart Citation
“…If improperly managed postoperatively, iatrogenic durotomies can increase the risk of developing refractory headache, intracranial hypotension, pseudomeningoceles, or, in rare cases, remote cerebellar hemorrhage 12,[22][23][24][25] . The UBS has been utilized in spine surgery with the proposed advantage of decreased operative times, higher volume of bone graft retention, and possibly fewer incidental durotomies 14 . While previous studies have reported improved operative speed and decreased complications for laminectomies performed by the UBS in the cervical and thoracic regions, the efficacy of the UBS for lumbar laminectomies has remained understudied 14,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasonic bone scalpel (UBS) is a tool that uses high-frequency oscillation to create localized tissue disruption 13 . By vibrating at high frequency, micromovements of the blade surface preferentially cut through hard surfaces such as bone 14 . This preferential cutting occurs because the higher natural elasticity of soft tissue structures such as the dura mater allows greater tolerance of vibratory strain 15 .…”
Section: Introductionmentioning
confidence: 99%